Components for use in energy storage or energy conversion devices and methods of manufacture thereof - Patents.com

JP2024518874A5Pending Publication Date: 2025-02-28ILIKA TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023560766
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-29
Filing Date
2022-04-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Traditional cold sintering processes for energy storage and conversion devices face issues with components delaminating from substrates due to lateral expansion and relaxation, limiting device size and layer thickness control.

Method used

A component design featuring a first part with ceramic particles and a second part with a sheet having through-thickness openings, where the second part is partially or fully embedded in the first part, allowing for uniaxial pressure application without mold constraints, enhancing adhesion and reducing internal resistance.

Benefits of technology

The design ensures robust attachment of sintered components to substrates, increases energy density, and reduces internal resistance by minimizing delamination, facilitating larger device sizes and precise thickness control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

A component for use in an energy storage or energy conversion device includes a first portion and a second portion, the first portion including particles of a ceramic material and the second portion provided by a sheet having a plurality of through-thickness openings, the second portion being at least partially embedded in the first portion.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to components for use in energy storage or energy conversion devices, in particular for use in batteries, capacitors, fuel cells (including solid oxide fuel cells and polymer electrolyte fuel cells), photovoltaic devices, piezoelectric devices, or thermoelectric converters, and methods for their manufacture. [Background technology]

[0002] Energy storage or conversion devices, such as batteries, capacitors, fuel cells (including solid oxide fuel cells and polymer electrolyte fuel cells), photovoltaic devices, piezoelectric devices, or thermoelectric converters, are typically composed of components that are produced by sintering of ceramic particles. However, high temperatures (e.g., greater than 1000 °C) are often required to produce properly sintered components. The application of such temperatures often results in undesirable side effects such as chemical decomposition, reactions between different materials forming harmful secondary phases, and / or evaporation of volatile species. Furthermore, the use of these high temperatures may be incompatible with the presence of other components of the device during the sintering process.

[0003] A known method of sintering ceramic components at low temperatures is cold sintering, as described, for example, in WO 2017 / 058727, which is incorporated herein by reference. Cold sintering can be defined as a process in which a sintered material is prepared by wetting at least one inorganic compound in particulate form with a solvent capable of partially solubilizing the inorganic compound, and then applying pressure and heat to the particles of the wetted inorganic compound to evaporate the solvent and compact the inorganic compound to form a sintered material. Usually, the wetted particles are heated to a temperature not exceeding 200° C. above the boiling point of the solvent at atmospheric pressure. In some cases, the wetted particles are heated to an absolute temperature of 250° C. or less.

[0004] It would be desirable to develop manufacturing procedures for energy storage or energy conversion device components that allow for the use of cold sintering.

[0005] In particular, it is desirable to develop such manufacturing procedures for components of battery cells, such as solid-state lithium-ion battery cells.

[0006] A solid-state lithium-ion battery cell is a type of rechargeable battery cell that uses lithium ions (Li + ) moves from the negative electrode (anode) to the positive electrode (cathode) during discharge and back again during charging. The electrodes can each reversibly store lithium ions and are separated by a bulk solid electrolyte that allows ion transport.

[0007] Additional components such as a current collector, an interfacial modifier, and / or an encapsulation or other protective element may also be provided. In some cases, the negative electrode is not present in the battery cell immediately after assembly of the cell, but instead is provided as a lithium anode that is formed during initial charging of the battery cell.

[0008] Solid-state battery cells potentially offer several advantages over liquid electrolyte lithium-ion battery cells, such as increased energy density, increased power density, lower leakage current and / or reduced flammability, etc. Thus, solid-state battery cells are being considered for use in, for example, electric vehicles and consumer electronics.

[0009] For large solid-state battery cells (such as for electric vehicles), components such as electrodes are typically manufactured by sintering particles of the constituent materials. In general, for energy storage and conversion devices, it is desirable to reduce the sintering temperature for the reasons discussed above, and also or instead to help reduce the evaporative loss of Li during sintering. Summary of the Invention [Problem to be solved by the invention]

[0010] Previous cold sintering processes involved applying pressure and heat to a mixture of inorganic particles and a solvent while holding the mixture in a mold. However, using a mold in this manner is undesirable when producing components of energy storage or energy conversion devices, as it would limit the size of the devices that can be provided and / or make precise control of the thickness of the layers in the device more difficult. Instead, it is preferred to apply uniaxial pressure to the mixture of particles and solvent in the absence of lateral constraints such as mold walls.

[0011] However, as a result of this, the mixture tends to expand laterally when placed under pressure during the sintering process, followed by a tendency for the sintered components to relax when the pressure is removed. As a result, the sintered components may delaminate from the underlying substrate when the pressure is removed. This may prevent the use of one-step procedures, such as, for example, sintering battery cell electrodes directly onto battery cell current collectors.

[0012] Surprisingly, it has been found that these problems may be alleviated by disposing the particle-solvent mixture on a mesh, or more generally on a substrate having a plurality of openings through its thickness. It is believed that this arrangement allows the particles to penetrate the openings in the substrate when the particle-solvent mixture is placed under pressure and sintered. As a result, the resulting sintered component remains attached to the substrate after the pressure is removed. It is believed that a step of partially or totally embedding the substrate in the sintered component may also help strengthen the component. [Means for solving the problem]

[0013] Thus, in a first aspect, the present invention provides a component for use in an energy storage or energy conversion device, the component comprising a first portion and a second portion, the first portion comprising particles of a ceramic material and the second portion provided by a sheet having a plurality of through-thickness openings, the second portion being at least partially embedded in the first portion.

[0014] The second portion may be partially or wholly embedded in the first portion.

[0015] For example, the second portion may be embedded to a depth in the range of 5 to 200 μm. In this case, the range of 5 to 200 μm represents the thickness of the portion of the first portion that is between the adjacent surfaces of the second portion and the first portion. In some cases, the second portion may be embedded to a depth in the range of 5 to 100 μm. In some cases, the second portion may be embedded to a depth in the range of 5 to 50 μm.

[0016] Typically, the component includes a sintered ceramic inclusion having a sheet partially or completely embedded therein that has a plurality of through-thickness openings.

[0017] The term ceramic refers to an inorganic, non-metallic material. The ceramic material may be selected from the group consisting of an electrode active material, an electrolyte, a piezoelectric material, a photovoltaic material, and a thermoelectric material. For the avoidance of doubt, other materials, for example particles of a further ceramic material, may also be present in the first portion of the component.

[0018] Typically, the component is an electrode.

[0019] In some cases, the component may be an electrode for a battery cell, such as a solid-state battery cell. In such cases, the electrode may have a thickness in the range of 70 to 1000 μm.

[0020] In some cases, the component may be an electrode for a battery cell that includes a liquid electrolyte. In such cases, the electrodes of the battery cell may be held apart by a separator, such as a porous polymer membrane. The liquid electrolyte, in turn, provides an ionically conductive medium that allows ion transport between, and possibly within, the electrodes. When the first portion of the component is a sintered ceramic-containing body, this typically provides sufficient porosity for the liquid electrolyte to permeate the component when used as an electrode, enhancing ion transport within the battery and reducing internal resistance.

[0021] In some cases, the component may be an electrode for a battery cell and the ceramic material may be an active electrode material, which may be a positive or negative active electrode material.

[0022] The positive electrode active material may be a lithium-containing material, a sodium-containing material, or a magnesium-containing material. Typically, the positive electrode active material is a lithium-containing material.

[0023] The positive electrode active material particles are lithium nickel cobalt aluminum oxide (LiNi x Co y Al z O2, x>0, y>0, z>0 and x+y+z=1), lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4), lithium manganese nickel oxide (LiMn 1.5 Ni 0.5 O4), lithium cobalt phosphate (LiCoPO4), lithium nickel cobalt manganese oxide (LiNi x Co y Mn z The positive electrode active material may include at least one selected from the group consisting of vanadium oxide (V2O5), LiVOPO4, Li3V2(PO4)3, and LiMPO4 (M=Ni, Mn).

[0024] The particles of the negative electrode active material are lithium titanate oxide (Li4Ti5O 12or Li2TiO3), and tin oxide.

[0025] In some cases, the particles of electrode active material may include a first electrode active material coated with a second electrode active material.

[0026] In some cases, the second portion of the component is provided by a sheet of conductive material.

[0027] For example, the second portion may include a metal or metal alloy. The metal or metal alloy may be selected from the group consisting of iron, steel (including stainless steel, i.e., steel containing at least 10 wt% or more chromium), nickel, nickel-based alloys containing at least 50 wt% or more nickel, copper, copper-based alloys containing at least 50 wt% or more copper, aluminum, aluminum-based alloys containing at least 50 wt% aluminum, platinum, and platinum-based alloys containing at least 50 wt% platinum. Thus, the second portion may include a metal or metal alloy containing one or more atomic elements selected from the group consisting of iron, nickel, copper, aluminum, titanium, and platinum.

[0028] When the component is an electrode of a battery cell, the use of a sheet of conductive material for the second part of the component may allow the second part to function as a current collector of the battery cell. By providing a current collector with a plurality of openings through its thickness, the weight of the current collector may be reduced. Thus, the energy density of the battery cell may be increased. Furthermore, since the sheet is partially or entirely embedded in the first part of the component, the interfacial contact area between the electrode active material and the sheet may be increased compared to a configuration in which the current collector is provided as a separate layer with a planar interface with the electrode. This may reduce the internal resistance of the battery cell.

[0029] In other cases, the second portion of the component may include a polymeric material. The presence of such a sheet may help strengthen the component.

[0030] In some cases, the second portion of the component has a density of 0.005 to 0.1 g / cm 2 In some cases, the second portion has a weight per unit area in the range of 0.01 to 0.05 g / cm. 2 Typically, the second portion has a weight per unit area in the range of 0.1 g / cm 2 Less than 0.05 g / cm 2 less than 0.04 g / cm 2 It has a weight per unit area of ​​less than 100 mm.

[0031] Preferably, the second portion has a maximum thickness in the range of 50 to 300 μm. If the second portion is a woven mesh, the maximum thickness may be at the point where two strands of the mesh cross.

[0032] Typically, the plurality of thickness direction openings in the second portion are arranged in a regular array, for example, the plurality of thickness direction openings may be arranged in a lattice pattern.

[0033] For the avoidance of doubt, the term "thickness opening" may be defined as an opening that extends directly laterally across the sheet from a first surface of the sheet to an opposing second surface of the sheet.

[0034] In some cases, a sheet having a plurality of through-thickness openings may be provided by a sheet having a plurality of through-thickness perforations, such as a grid.

[0035] Generally, however, the second part is provided by a woven mesh. Generally, woven meshes containing metal or metal alloy strands are commercially available in a variety of types, differing in the number of strands per unit distance measured in a direction perpendicular to the strands. If the mesh has a low number of strands per unit distance, the thickness of the individual strands tends to be high, which tends to increase the mesh weight per unit area. Therefore, it is generally preferable to avoid meshes with a very low number of strands per unit distance. Conversely, if the mesh has a high number of strands per unit distance, the gaps between the strands may be small, making it difficult to provide a component in which the second part is firmly embedded in the first part.

[0036] Typically, woven mesh has 5-500 strands per cm, measured perpendicular to the strands. In some cases, woven mesh has 30-250 strands per cm, measured perpendicular to the strands. In other cases, woven mesh has 30-100 strands per cm, measured perpendicular to the strands.

[0037] In general, it is desirable for the plurality of through-thickness openings in the second portion to be sized to allow passage of grains of ceramic material therethrough during manufacture of the electrode.

[0038] Typically, the particles of the ceramic material have a d50 size in the range of 10 nm to 50 μm, as measured using laser diffraction of a dispersion of the particles according to ISO 13320:2020. For example, the particles of the ceramic material may have a d50 size in the range of 100 nm to 40 μm. In some cases, the particles of the ceramic material may have a d50 size in the range of 1-40 μm. In some cases, the particles of the ceramic material may have a d50 size in the range of 2-20 μm.

[0039] Therefore, the plurality of thickness-direction openings in the second portion typically have a width in the range of 10 to 1000 μm. For example, the plurality of openings may have a width in the range of 10 to 200 μm.

[0040] The smaller the plurality of openings, the thinner, and thus lighter, the sheet that can be provided as the second portion. Therefore, in some cases, the plurality of openings have a width in the range of 50 - 200 μm.

[0041] The width of the opening is the smaller dimension of the opening in the plane of the sheet providing the second portion. Typically, the plurality of openings have a square shape. In such a case, the width of the opening corresponds to the length of one side of the square. In some cases, the plurality of openings may be circular. In such a case, the width of the opening corresponds to the diameter of the circle. In some cases, the plurality of openings may have a rectangular shape. In such a case, the width of the opening corresponds to the length of the shorter side of the rectangle.

[0042] Generally, when the component is an electrode for a battery cell and the ceramic material is an electrode active material, the first portion further includes an ion-conductive component distributed among the particles of the electrode active material. The ion-conductive component may be a lithium-containing material, a sodium-containing material, or a magnesium-containing material. Generally, the ion-conductive component is a lithium-containing material.

[0043] The ion-conductive component is LAGP (Li 1.5 Al 0.5 Ge 1.5 (PO4)3); LATP (Li 1.3 Al 0.3 Ti 1.7 (PO4)3); NASICON (Na 1+x Zr2Si x P 3ーx O 12 , 0 < x < 3); LISICON (Li 2+2x Zn 1ーx GeO4, 0 < x < 1); lithium-ion conductive glass ceramics (Ohara Inc.) (LICGC TM); lithium-loaded garnets. A La B M C Zr D O E Compounds having the formula: <A<8.5、1.5<B<4、0≦C≦2、0≦D<2、10<E<13およびM=Al、Mo、W、Nb、Sb、Ca、Ba、Sr、Ce、Hf、Rb、またはTaである。

[0044] The ionically conductive component may further comprise at least one electrolyte salt, such as one or more salts selected from the group consisting of LiTFSI (lithium bis(trifluoromethanesulfonyl)imide); LiFSI (lithium bis(fluorosulfonyl)imide) and lithium perchlorate.

[0045] Typically, the ionically conductive component has an ion conductivity of at least 10 as measured by impedance spectroscopy at 25° C. -8 Scm -1 In certain embodiments, the ion conductivity of the ionically conductive component is at least 10 -6 Scm -1 In certain embodiments, the ionic conductivity of the ionically conductive component may be at least 10 -5 Scm -1 In certain embodiments, the ionic conductivity of the ionically conductive component may be at least 10 -4 Scm -1 It may be.

[0046] Typically, the ionically conductive component is present in the first portion in an amount of 10 to 50 vol % based on the total volume of the particles of the electrode active material. In certain cases, the ionically conductive component is present in the first portion in an amount of 20 to 40 vol % based on the total volume of the particles of the electrode active material.

[0047] It is believed that when the second part is provided by a sheet of conductive material, the component being an electrode for a battery cell, and the ceramic material is the electrode active material, the presence of such a sheet in the electrode may reduce or even eliminate the need for an additional electronically conductive component distributed between the particles of the electrode active material of the first part. The energy density of the electrode may thus be increased. For example, the amount of the additional electronically conductive component distributed between the particles of the electrode active material may be less than 10 vol% relative to the total volume of the particles of the electrode active material. Preferably, the amount of the additional electronically conductive component distributed between the particles of the electrode active material may be less than 5 vol% relative to the total volume of the particles of the electrode active material. More preferably, the amount of the additional electronically conductive component distributed between the particles of the electrode active material may be less than 2 vol% relative to the total volume of the particles of the electrode active material. Even more preferably, the amount of the additional electronically conductive component distributed between the particles of the electrode active material may be less than 1 vol% relative to the total volume of the particles of the electrode active material.

[0048] If an additional electronically conductive component is present, it typically has a thermal conductivity of at least 10 as measured by DC decay measurements at 25° C. -4 Scm -1 In certain embodiments, the electronic conductivity of the additional electronically conductive component is at least 10 -3 Scm -1 In certain embodiments, the electronic conductivity of the additional electronically conductive component may be at least 10 -2 Scm -1 In certain embodiments, the electronic conductivity of the additional electronically conductive component may be at least 10 -1 Scm -1 In certain embodiments, the electronic conductivity of the additional electronically conductive component may be at least 1 S cm -1 In certain embodiments, the electronic conductivity of the additional electronically conductive component may be at least 10 S cm -1 It may be.

[0049] When present, the electronically conductive component may be provided by a carbon material, which may typically be selected from the group consisting of carbon black, acetylene black, activated carbon, carbon nanotubes, carbon fibers, and mixtures thereof. Alternatively, the electronically conductive component may be provided by a metallic material.

[0050] Generally, when the component is an electrode of a battery cell and the ceramic material is an electrode active material, The particles of electrode active material are present in the first portion in an amount of at least 50 vol% relative to the volume of the first portion. In general, it is preferred that the first portion contains a large amount of electrode active material to increase the capacity of the battery cell. Thus, in some cases, the particles of electrode active material are present in the first portion in an amount of at least 60 vol% relative to the volume of the first portion. In some cases, the particles of electrode active material are present in the first portion in an amount of at least 70 vol% relative to the volume of the first portion. In some cases, the particles of electrode active material are present in the first portion in an amount of at least 80 vol% relative to the volume of the first portion. Thus, for example, the particles of electrode active material may be present in the first portion in an amount of 50-80 vol% relative to the volume of the first portion.

[0051] For the avoidance of doubt, the volume percentages of material of the first portion are quoted for that part of the first portion which does not have any second portion embedded therein.

[0052] Generally, the component is thicker than the sheet. Typically, the thickness of the component will be at least 30% greater than the thickness of the sheet. In some cases, the thickness of the component will be at least 50% greater than the thickness of the sheet. In yet other cases, the thickness of the component will be at least 80% greater than the thickness of the sheet. For the avoidance of doubt, the thickness of the component is measured in the same direction as the thickness of the sheet.

[0053] In a second aspect, the invention may provide a method of manufacturing a component according to the first aspect of the invention, the method comprising the steps of providing a sheet having a plurality of through-thickness openings, combining particles of a ceramic material with a liquid phase to form a slurry, depositing the slurry on the sheet having a plurality of through-thickness openings, wetting the particles of the ceramic material with a solvent configured to partially solubilize the ceramic material after depositing the slurry on the sheet, and sintering the particles of the wet ceramic material by applying pressure and heat to the particles to evaporate the solvent and compact the ceramic material, the sintering temperature being no more than 200° C. above the boiling point of the solvent.

[0054] For the avoidance of doubt, pressure and heat are simultaneously applied to the wetted particles to evaporate the solvent and compact the ceramic material. Furthermore, the step of wetting particles of ceramic material with a solvent configured to partially solubilize the ceramic material may effectively correspond to the step of wetting particles of ceramic material with a solvent that partially solubilizes the ceramic material.

[0055] Generally, wetting the particles of ceramic material with a solvent involves applying the solvent to the particles in the form of a solvent vapor or by a spraying process.

[0056] Typically, the liquid phase includes a polymer binder phase, and the method further includes, after the step of depositing the slurry onto the sheet and prior to the step of wetting the particles of the ceramic material with the solvent, The method includes heating the slurry to reduce the concentration of the polymeric binder phase in the slurry, which typically involves holding the slurry at a temperature in the range of 180-260° C. for a period of time of about 20 minutes or less.

[0057] Typically, the liquid phase comprises a polymeric binder phase that is dissolved in an organic medium, such as a polycarbonate. Generally, the organic medium is non-aqueous.

[0058] Usually, the sintering temperature is not more than 150° C. above the boiling point of the solvent. In some cases, the sintering temperature is not more than 100° C. above the boiling point of the solvent. The boiling point of the solvent refers to the boiling point at atmospheric pressure.

[0059] Typically, the sintering temperature is 300° C. or less. In some cases, the sintering temperature is 250° C. or less. In some cases, the sintering temperature is 225° C. or less. In some cases, the sintering temperature is 200° C. or less. In some cases, the sintering temperature is 175° C. or less. In some cases, the sintering temperature is 150° C. or less.

[0060] Generally, the sintering temperature is at least 50°C. In some cases, the sintering temperature is at least 100°C. Thus, the sintering temperature may be in the range of 50-300°C, such as 50-250°C, 50-225°C, 50-200°C, 50-175°C, or 50-150°C. Alternatively, the sintering temperature may be in the range of 100-250°C, such as 100-225°C, 100-200°C, 100-175°C, or 100-150°C. For the avoidance of doubt, the sintering temperature is the maximum temperature reached during the sintering step.

[0061] Typically, the applied pressure is 300 MPa or less. Optionally, the applied pressure is 200 MPa or less. Optionally, the applied pressure is 150 MPa or less. Optionally, the applied pressure is 100 MPa or less. Optionally, the applied pressure is 50 MPa or less.

[0062] Typically, the applied pressure is at least 10 MPa. In some cases, the applied pressure is at least 20 MPa. Thus, the applied pressure may be in the range of 10-300 MPa, for example, 10-200 MPa, 10-150 MPa, 10-100 MPa, or 10-50 MPa. Alternatively, the applied pressure may be in the range of 20-300 MPa, for example, 20-200 MPa, 20-150 MPa, 20-100 MPa, or 20-50 MPa.

[0063] Typically, the step of sintering the particles of ceramic material by applying pressure and heat to evaporate the solvent and compress the ceramic material takes no longer than 60 minutes. In some cases, this step may take less than 30 minutes. In some cases, this step may take less than 20 minutes.

[0064] Typically, this procedure takes at least 5 minutes. Thus, the time required for this step may range from 5 to 60 minutes, for example from 5 to 30 minutes or from 5 to 20 minutes.

[0065] Typically, the slurry is deposited through a mask onto a sheet having a plurality of through-thickness openings.

[0066] In some cases, the slurry is deposited on a sheet having multiple thickness openings by a sheet-to-sheet process. The sheet-to-sheet process is typically an intermittent process and may include processes such as tape casting, screen printing, etc. In other cases, the deposition process may be a roll-to-roll process. The roll-to-roll process is typically a continuous process and may include processes such as comma bar, K-bar, doctor blade, slot die, flexographic, gravure, intaglio, and lithographic coating. Detailed descriptions and requirements of these processes are disclosed in "The Printing Ink Manual" RH Leach and RJ Pierce eds. 5thed 1993 (ISBN 0 9448905 81 6), which is incorporated herein by reference.

[0067] In some cases, the sheet having a plurality of thickness-wise openings is a sheet of conductive material.

[0068] In some cases, the solvent may be an aqueous solvent. In some cases, the solvent may be an organic solvent. Generally, the solvent is selected from the group consisting of water, acetic acid, polycarbonate, dimethylformamide, and benzyl alcohol.

[0069] In some cases, the component is an electrode of a battery cell, and the ceramic material is an electrode active material. In such a case, the slurry is LAGP (Li 1.5 Al 0.5 Ge 1.5 (PO4)3); LATP (Li 1.3 Al 0.3 Ti 1.7 (PO4)3); NASICON (Na 1+x Zr2Si x P 3-x O 12 , 0 < x < 3); LISICON (Li 2+2x Zn 1-x GeO4, 0 < x < 1); lithium ion conductive glass ceramics (Ohara Corporation) (LICGC TM ); and may further contain particles of an ion conductive material such as garnet filled with lithium. The formula Li A La B M C Zr D O E having a compound is included, where 4 < A < 8.5, 1.5 < B < 4, 0 ≤ C ≤ 2, 0 ≤ D < 2, 10 < E < 13, and M = Al, Mo, W, Nb, Sb, Ca, Ba, Sr, Ce, Hf, Rb, or Ta. Generally, the ion conductive material may be a lithium-containing material, a sodium-containing material, or a magnesium-containing material. Typically, the ion conductive material is a lithium-containing material.

[0070] In some cases (particularly when the component is an electrode for a battery cell and the ceramic material is the electrode active material), the slurry may include one or more electrolyte salts, such as one or more salts selected from the group consisting of LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiFSI (lithium bis(fluorosulfonyl)imide) and lithium perchlorate, and mixtures thereof. Alternatively, the one or more electrolyte salts may be dissolved in a solvent used to wet the particles of the ceramic material.

[0071] In some cases (particularly when the component is an electrode for a battery cell and the ceramic material is an electrode active material), the slurry may include a solid electronically conductive component. However, it is believed that the amount of solid electronically conductive component in the slurry may be reduced when the sheet on which the slurry is deposited is a sheet of conductive material. For example, the amount of solid electronically conductive component may be less than 10 vol% relative to the total volume of the particles of the ceramic material (which may be the electrode active material). Preferably, the amount of solid electronically conductive component may be less than 5 vol% relative to the total volume of the particles of the ceramic material (which may be the electrode active material). Preferably, the amount of solid electronically conductive component may be less than 2 vol% relative to the total volume of the particles of the ceramic material (which may be the electrode active material). Preferably, the amount of solid electronically conductive component may be less than 1 vol% relative to the total volume of the particles of the ceramic material (which may be the electrode active material).

[0072] The sheet onto which the slurry is deposited may have one or more of the features of the second part of the component according to the first aspect of the invention.

[0073] The particles of ceramic material may have one or more of the characteristics of particles of ceramic material present in the electrode according to the first aspect of the present invention, For the avoidance of doubt, particles of other materials, for example further ceramic materials, may be present in the slurry.

[0074] Typically, the particles of the ceramic material have a d50 size in the range of 2 to 50 μm, as measured using laser diffraction of a dispersion of the particles according to ISO 13320:2020. For example, the particles of the ceramic material may have a d50 size in the range of 2 to 40 μm. In some cases, the particles of the ceramic material may have a d50 size in the range of 5 to 40 μm. In some cases, the particles of the ceramic material may have a d50 size in the range of 5 to 20 μm.

[0075] In a third aspect, the invention may provide a method of manufacturing a component according to the first aspect of the invention, the method comprising the steps of: providing a sheet having a plurality of through-thickness openings, combining particles of the ceramic material with a solvent, the solvent being configured to solubilize the ceramic material, to form a slurry, depositing the slurry on the sheet having a plurality of through-thickness openings, and sintering the particles of the ceramic material by applying pressure and heat to the slurry to evaporate the solvent and compact the ceramic material, the sintering temperature being no more than 200° C. above the boiling point of the solvent.

[0076] For the avoidance of doubt, pressure and heat are simultaneously applied to a mixture of particles of ceramic material and solvent present in a slurry.

[0077] Typically, the slurry further comprises a polymeric binder, and the method further comprises, after the step of sintering the slurry to compact the ceramic material, heating the compacted material to a temperature above the sintering temperature to reduce the concentration of the polymeric binder phase in the compacted material, which typically comprises holding the compacted material at a temperature in the range of 180-260° C. for a time period of about 20 minutes or less.

[0078] The method according to the third aspect of the invention may have the advantage, compared to the method according to the second aspect of the invention, that only one solvent is required, whereas the method according to the second aspect requires a liquid phase and a solvent provided in separate steps. However, it is believed that any step of applying heat to reduce the concentration of the polymeric binder phase present may require more care if this step is carried out after compaction of the ceramic material.

[0079] The method according to the third aspect of the invention may include one or more of any of the features of the method according to the second aspect of the invention, such as features relating to the sintering temperature, the pressure applied, the sintering time, the method of depositing the slurry on the sheet, and the amount and type of material used.

[0080] In a fourth aspect, the invention may provide a method of manufacturing a component according to the first aspect of the invention, the method comprising the steps of providing a sheet having a plurality of through-thickness openings, combining particles of a ceramic material with a solvent to form a slurry such that the solvent partially solubilizes the ceramic material, depositing the slurry on the sheet having a plurality of through-thickness openings, and sintering the particles of the ceramic material by simultaneously applying pressure and heat to the slurry to evaporate the solvent and compact the ceramic material, the sintering temperature being no more than 200° C. above the boiling point of the solvent.

[0081] For the avoidance of doubt, pressure and heat are simultaneously applied to a mixture of particles of ceramic material and solvent present in a slurry.

[0082] Typically, the slurry further comprises a polymeric binder, and the method further comprises, after the step of sintering the slurry to compact the ceramic material, heating the compacted material to a temperature above the sintering temperature to reduce the concentration of the polymeric binder phase in the compacted material, which typically comprises holding the compacted material at a temperature in the range of 180-260° C. for a time period of about 20 minutes or less.

[0083] The method according to the fourth aspect of the invention may include one or more of any of the features of the method according to the second aspect of the invention, such as features relating to the sintering temperature, the pressure applied, the sintering time, the method of depositing the slurry on the sheet, and the amount and type of material used.

[0084] In a fifth aspect, the present invention may provide a component for use in an energy storage or energy conversion device, the component being obtained or obtainable through a method according to the second, third or fourth aspect of the invention.

[0085] The component may be an electrode of a battery cell.

[0086] In a sixth aspect, the present invention may provide an energy storage or energy conversion device comprising a component according to the first or fifth aspects of the invention. The device may be selected from the group consisting of a battery, a capacitor, a fuel cell (including solid oxide fuel cells and polymer electrolyte fuel cells), a photovoltaic device, a piezoelectric device, and a thermoelectric converter.

[0087] In some cases, the device may be a battery cell including an electrode provided by a component according to the first or fifth aspect of the invention, and the battery cell may further include an electrolyte layer disposed on a surface of the electrode.

[0088] Typically, an electrolyte layer is disposed on the face of the electrode distal from the second portion. [Brief description of the drawings]

[0089] The invention will now be described by way of example with reference to the following figures: [Figure 1] 1a to 1f are scanning electron microscope photographs showing cross-sectional views of Example 1, Example 2, Example 3, Example 8, Example 4, and Example 5, respectively. [Diagram 2]1 is a graph showing normalized capacity versus cycle number for battery cells including the cathode of Example 3. [Diagram 3] 13 is a graph showing the relationship between time and pressure for a battery cell including the cathode of Example 3. [Figure 4] 1 is a graph showing mesh weight per unit area versus mesh size. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0090] [Preparing the cathode] A slurry was prepared from the ingredients listed in Table 1. First, the binder and electrolyte salt were dissolved in a solvent, and then the solvent was mixed with the remaining ingredients. The mixing process was carried out in a planetary bowl mixer, first at 1000 rpm for 10 minutes, followed by 800 rpm for 5 minutes. [Table 1]

[0091] Two NMC grades were used and their properties are shown in Table 2. Particle size analysis was carried out using laser diffraction of particle dispersions according to ISO 13320:2020. [Table 2]

[0092] Examples 1-12 were prepared by screen printing the slurries onto a metal woven mesh through a mask with openings 500 μm thick and 30-35 mm in diameter.

[0093] Comparative Examples 1-4 were prepared by screen printing the slurries onto metal foil through a mask having openings 500 μm thick and 30-35 mm in diameter.

[0094] The mask was then removed and the sample was heated at a rate of 0.5° C. / min to 250° C. and held at this temperature for 6 minutes to remove the organic binder phase.

[0095] Water was then sprayed onto the surface of the screen-printed sample to wet and partially solubilize the particles of the electrode active material.

[0096] The samples were then placed in a heated uniaxial press and sintered at 130 °C with a pressure of 30.59 MPa and held for 10 min.

[0097] Once the sintering step was complete, the samples were removed from the press and inspected to assess the quality of adhesion of the sintered material to the mesh or foil substrate. Adhesion quality was defined according to the following categories: · Weak adhesion: the sintered material did not adhere to the substrate at all. Moderate adhesion: The sintered material initially adhered to the substrate but easily peeled off when, for example, trying to cut the sample through its thickness. Good adhesion: The sintered material remained adhered to the substrate even when attempts were made to cut the sample. [Table 3] [Table 4]

[0098] Cross-sectional views of Example 1, Example 2, Example 3, Example 8, Example 4, and Example 5 are shown in Figs. 1a to 1f, respectively.

[0099] [Battery cell] A battery cell was fabricated using the electrodes of Example 3, the LAGP / polymer electrolyte, a lithium anode and a copper current collector. After the battery was formed, electrochemical testing was performed using the following procedure. Charging = Charge with constant current up to a voltage of 4.2V, then hold the battery at this voltage for 60 minutes. Discharge: Discharge at a constant current up to a voltage of 2.7V The results are shown in Figures 2 and 3, which show that the cycle was successfully completed with high efficiency after the forming stage.

[0100] [Mesh weight] FIG. 4 is a graph of mesh weight per unit area versus mesh size for stainless steel, aluminum, and nickel meshes, including a band showing the weight per unit area for a typical 50 μm thick stainless steel foil. This shows that the finer meshes (e.g., aluminum mesh with mesh size 120, stainless steel mesh with mesh sizes 200 and 500) have a lower weight per unit area than the 50 μm thick stainless steel foil. This may help increase the energy density per unit weight of a battery including an electrode according to the present invention.

Claims

1. 1. A component for use in an energy storage or energy conversion device, comprising: the component comprises a first portion and a second portion; the first portion includes particles of a ceramic material and the second portion is provided by a sheet having a plurality of through-thickness openings; the second portion is at least partially embedded in the first portion. Component.

2. The ceramic material is Selected from the group consisting of electrode active materials, electrolytes, piezoelectric materials, photovoltaic materials, and thermoelectric materials; 2. The component of claim 1.

3. the second portion being provided by a sheet of conductive material; 2. The component of claim 1.

4. the second portion comprises a metal or a metal alloy; 4. The component of claim 3.

5. The metal or metal alloy comprises one or more elements selected from the group consisting of iron, nickel, copper, aluminum, titanium, and platinum; 5. The component of claim 4.

6. The openings in the thickness direction are arranged in a lattice pattern. Component according to claim 1

7. the second portion being provided by a woven mesh; 7. The component of claim 6.

8. The woven mesh has 5-500 strands per cm, measured perpendicular to the strands.

8. The component of claim 7.

9. The woven mesh has 30-250 strands per cm, measured perpendicular to the strands.

9. The component of claim 8.

10. The woven mesh has 30-100 strands per cm, measured perpendicular to the strands.

10. The component of claim 9.

11. The opening has a width in the range of 10-1000 μm.

2. The component of claim 1.

12. The opening has a width in the range of 10-200 μm.

12. The component of claim 11.

13. The opening has a width in the range of 50-200 μm.

13. The component of claim 12.

14. The component is an electrode for a battery cell, in particular a solid-state battery cell, and the ceramic material is an electrode active material; 2. The component of claim 1.

15. The particles of the electrode active material are Lithium Nickel Cobalt Aluminum Oxide (LiNi x Co y A z O 2 , x>0, y>0, z>0 and x+y+z=1), lithium cobalt oxide (LiCoO 2 ), lithium iron phosphate (LiFePO 4 ), lithium manganese nickel oxide (LiMn 1.5 Ni 0.5 O 4 ), lithium cobalt phosphate (LiCoPO 4 ), lithium nickel cobalt manganese oxide (LiNi x Co y Mn z O 2 , x>0, y>0, z>0, x+y+z=1), vanadium oxide (V 2 O 5 ), LiVOPO 4 , Li 3 V 2 (P.O. 4 ) 3 , LiMPO 4 (M=Ni, Mn), tin oxide and lithium titanate oxide (Li 4 Ti 5 O 12 Or Li 2 TiO 3 ), At least one electrode active material selected from the group consisting of:

15. The component of claim 14.

16. the first portion further comprises an ionically conductive component distributed between particles of the electrode active material; 15. The component of claim 14.

17. The amount of electronically conductive component in the first portion of the electrode is less than 10 vol% based on the total volume of the electrode active material.

15. The component of claim 14.

18. A method for manufacturing a component according to claim 1, comprising the steps of: Providing a sheet having a plurality of through-thickness openings; combining particles of a ceramic material with a liquid phase to form a slurry; depositing the slurry onto the sheet having the plurality of through-thickness openings; after depositing the slurry on the sheet, wetting the particles of the ceramic material with a solvent configured to partially solubilize the ceramic material; sintering the particles of the wet ceramic material by applying pressure and heat to the particles to evaporate the solvent and compact the ceramic material; Including, The sintering temperature is 200° C. or less above the boiling point of the solvent; method.

19. The step of wetting the particles of the ceramic material with a solvent comprises: applying the solvent to the particles by a spraying process; 20. The method of claim 18.

20. The step of wetting the particles of the ceramic material with a solvent comprises: applying the solvent to the particles in the form of a vapor of the solvent; 20. The method of claim 18.

21. the liquid phase comprises a polymeric binder phase; The method comprises: after depositing the slurry on the sheet and prior to wetting the particles of the ceramic material with the solvent, heating the slurry to reduce the concentration of the polymeric binder phase in the slurry; Further including:

20. The method of claim 18.

22. A method for producing the electrode of claim 1, comprising the steps of: Providing a sheet having a plurality of through-thickness openings; combining particles of the ceramic material with a solvent configured to solubilize the ceramic material to form a slurry; depositing the slurry onto the sheet having a plurality of through-thickness openings; sintering the particles of the ceramic material by applying pressure and heat to the slurry to evaporate the solvent and compact the ceramic material; Including, The sintering temperature is 200° C. or less above the boiling point of the solvent; method.

23. The slurry further comprises a polymeric binder; after sintering the slurry to compact the ceramic material, heating the compacted material to a temperature above the sintering temperature to reduce the concentration of a polymer binder phase in the compacted material; Further comprising:

23. The method of claim 22.

24. The sintering temperature is 300° C. or less.

20. The method of claim 18.

25. The pressure applied is 300 MPa or less; 20. The method of claim 18.

26. sintering the particles of the ceramic material by applying pressure and heat to evaporate the solvent and compact the ceramic material takes a time period of 60 minutes or less.

20. The method of claim 18.

27. The particles of the ceramic material have a d50 size in the range of 10 nm to 50 μm.

20. The method of claim 18.

28. The slurry is deposited through a mask onto the sheet having the plurality of through-thickness openings.

20. The method of claim 18.

29. The slurry is deposited on the sheet having a plurality of through-thickness openings by tape casting or screen printing.

20. The method of claim 18.

30. The solvent is selected from the group consisting of water, acetic acid, polycarbonate, dimethylformamide, and benzyl alcohol; 20. The method of claim 18.

31. The component is an electrode for a battery cell, in particular a solid-state battery cell, and the ceramic material is an electrode active material; 20. The method of claim 18.

32. The slurry further comprises particles of an ionically conductive material.

32. The method of claim 31 .

33. The amount of solid electronically conductive component in the slurry is less than 10 vol% based on the total volume of the particles of electrode active material; 32. The method of claim 31 .

34. 1. A component for use in an energy storage or energy conversion device, comprising: Component obtained or obtainable by the method according to claim 18.

35. 2. A method for manufacturing a semiconductor device comprising: Energy storage or conversion devices.

36. The device, comprising: a device selected from the group consisting of a battery (including solid-state batteries), a capacitor, a fuel cell (including solid oxide fuel cells and polymer electrolyte fuel cells), a photovoltaic device, a piezoelectric device, and a thermoelectric converter.

36. An energy storage or energy conversion device as claimed in claim 35.

37. A solid-state battery cell including the components of claim 1, the component is an electrode, The solid-state battery cell further includes an electrolyte layer disposed on a surface of the electrode. Solid-state battery cells.